The Effectiveness of Dola AI in Teaching Descriptive Writing to EFL Student - Dinda Nur Khadijah; Hastuti Retno Kuspiyah; Eka Agustina (JLE: Journal of Literate of English Education Study Program, 2026)
The goal of this study is to determine whether there is a significant difference in EFL writing ability, specifically in writing descriptive texts, between students taught using Dola AI and students taught using conventional methods among eleventh-grade students at SMK PGRI 2 Belitang. A quasi-experimental method with a matching-only pre-test and post-test control group design was applied in this study. Through a purposive sampling technique, 45 students were selected as participants, consisting of 23 students in the experimental group (XI.4) and 22 students in the control group (XI.3). Writing tests, namely pre-tests and post-tests, were used to collect data, while data analysis was performed using SPSS 26, which included the Kolmogorov–Smirnov normality test, the Levene homogeneity test, and the independent samples t-test. This study yielded a significance value (two-tailed) of 0.006, which is less than 0.05 (0.006 < 0.05), indicating a statistically significant difference between the experimental and control groups. Additionally, the experimental group’s post-test mean score (87.09) was higher than the control group’s (79.50). These findings indicate that Dola AI is effective in improving students’ EFL writing ability, particularly in the areas of content, organization, vocabulary, grammar, and mechanics.